A Comparative Study of the Citation Impact of Chinese Journals with Government Priority Support - Zhou, Ping; Leydesdorff, Loet (Frontiers in Research Metrics and Analytics, 2016)
In order to improve the citation impact of Chinese journals, relevant Chinese government agencies have launched a program entitled Citation Impact Upgrading Plan (CIUP) with financial support. Only a few journals that perform better have been screened out for CIUP support. The current study tries to figure out if the screening results reflect the bibliometric status of the journals. We compare journals being supported by CIUP with unsupported ones. Journals supported by the CIUP have made progress in raising their JIF values and perform better in terms of JIF values. Journals citing CIUP journals have a spectrum of higher JIF values. Journals in a cited network of a CIUP journal are better integrated with one another. Wide gaps, however, still exist between Chinese and leading international journals. A network visualization of being-cited patterns can be used to measure a journal’s citation impact in relation to the JIF values of journals in the network. Policy suggestions on improving citation impact of Chinese journals will be proposed.